Strategic financial management : a managerial approach - Ali, Muhammad; Choi-Meng, Leong; Puah, Chin-Hong; Raza, Syed Ali; Sivanandan, Premagowrie (Emerald Publishing Limited, 2024)
The era of digital transformation brings to small and medium-sized enterprises new challenges and complex issues that need to be navigated carefully and effectively to keep pace with the rate of local and global changes, to continue operating efficiently and competitively. Strategic Financial Management is a comprehensive exploration of contemporary financial challenges from a managerial perspective with interesting and insightful chapters that address sustainability reporting, ESG integration, globalization's impact on financial strategies, and corporate governance. Investigating theoretical frameworks, identifying problems, and discussing implications for managers, entrepreneurs, and policymakers, regulatory changes and compliance challenges are dissected in this book, providing a timely guide for managers to navigate the evolving regulatory landscape. Managing financial talent is recognised as a crucial element in achieving organizational success, and the role of data management and analytics in finance is emphasised in informed decision-making, which are interwoven in the chapters of this book. Exploring the dynamics of financial communication and stakeholder relations, and acknowledging their pivotal role in maintaining organizational trust, the chapters contribute to the ongoing dialogue on sustainability, governance, and financial strategies. Strategic Financial Management provides valuable guidance for managers, entrepreneurs, and policymakers in navigating the complexities of the modern financial landscape.